Dimensional tailoring of nitrogen-doped graphene for high performance supercapacitors. Issue 60 (9th June 2016) - Lee, Seung Yong; Choi, Chang Hyuck; Chung, Min Wook; Chung, Jae Hoon; Woo, Seong Ihl
Abstract : In supercapacitors, one dimensional graphene ribbons which form net-like porous structure demonstrate low mass transfer resistance at low frequency region and a consequent efficient charge transferability. Abstract : Due to its unique properties, graphene has been regarded as a promising electrode material in various fields of energy conversion and storage devices. In supercapacitors, however, the graphene electrodes show unexpectedly poor energy densities due to low transferability of charge carriers in the randomly overlaid graphene electrodes. For efficient charge transfers, construction of three-dimensional graphene structures has been generally considered. In this study, contrary to previous strategies, the graphene structures are sequentially tailored from two-dimensional sheets to one-dimensional ribbons and zero-dimensional dots, and then their capacitive behaviors are investigated in a symmetric unit cell. Dimensionality of the graphene determines the local pore structure and morphology of the fabricated graphene electrodes. Hence, it strongly affects the transfer rate of charge carriers and capacitive performance. One-dimensional ribbons, which have a high length-to-width ratio and a consequent net-like porous structure in the fabricated electrode, demonstrate an efficient charge transferability with 378 F g −1 specific capacitance at 1 A g −1 current density in 6 M KOH electrolyte. Additionally, a durability study coupled with X-ray photoelectron spectroscopy (XPS) reveals that performance degradation of the graphene-based electrodes mainly results from surface oxidation which inhibits facile electron transfers.